2000
DOI: 10.1128/mcb.20.23.8720-8730.2000
|View full text |Cite
|
Sign up to set email alerts
|

8-Bromo-Cyclic AMP Induces Phosphorylation of Two Sites in SRC-1 That Facilitate Ligand-Independent Activation of the Chicken Progesterone Receptor and Are Critical for Functional Cooperation between SRC-1 and CREB Binding Protein

Abstract: ). To determine if other receptor-associated cofactors were targets of cAMP-dependent signaling pathways, we examined the phosphorylation of steroid receptor coactivator 1 (SRC-1). We detected a 1.8-fold increase in SRC-1 phosphorylation in transfected COS-1 cells incubated with 8-bromo-cAMP. Phosphorylation was increased on two mitogen-activated protein kinase (MAPK) sites, threonine 1179 and serine 1185. PKA did not phosphorylate these sites in vitro. However, blockage of PKA activity in COS-1 cells with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(179 citation statements)
references
References 60 publications
3
172
1
1
Order By: Relevance
“…In what may be the first evidence of this kind, Rowan et al [35,36] showed that steroid receptor co-activator-1 (SRC-1) contains several consensus sequences for phosphorylation by MAPK (ERK-1 and ERK-2), three of which were phosphorylated in vitro by ERK-2. More importantly, evidence was provided that potentiation of ligand-dependent, progesterone receptor-mediated transcription by EGF treatment of intact cells was mediated by SRC-1.…”
Section: Discussionmentioning
confidence: 99%
“…In what may be the first evidence of this kind, Rowan et al [35,36] showed that steroid receptor co-activator-1 (SRC-1) contains several consensus sequences for phosphorylation by MAPK (ERK-1 and ERK-2), three of which were phosphorylated in vitro by ERK-2. More importantly, evidence was provided that potentiation of ligand-dependent, progesterone receptor-mediated transcription by EGF treatment of intact cells was mediated by SRC-1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are several coactivators, including the p72/ p68 RNA-binding DEAD box proteins (64,65) and the RNA coactivator, SRA, 2 which have been found to interact selectively with the AF-1 domain of ER␣ but not that of ER␤. Moreover, in addition to p68 being a phosphorylated protein (66), all three of these coactivators are found in complexes with other coactivator molecules, such as CBP, SRC-1, TIF2, and AIB1 (64,65), which are known to be phosphoproteins (34,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…Forskolin/IBMX-stimulated ER␣ Activity Is Not Caused by cAMP/PKA-dependent SRC-1 Phosphorylation-It had been demonstrated previously that the chicken PR is not phosphorylated in response to cell treatment with 8-bromo-cAMP, but rather cAMP activation of transcription seems to be mediated by an increase in SRC-1 phosphorylation (34). Moreover, SRC-1 binds to both the EF domain of ER␣ as well as c-Jun (61, 62) and is therefore a good candidate for mediating indirect interactions between these two transcription factors, as described above.…”
Section: Functional Interactions With the Tre-bound Factor(s) Can Be mentioning
confidence: 99%
See 1 more Smart Citation
“…CBP has been shown in numerous studies to act as a nuclear receptor cofactor. Specifically it has been shown that CBP has a synergistic effect in combination with R5020 on the transcriptional activity of the chicken PR (39). In addition, CBP has been shown previously to associate with the MMTV array upon activation of GR and the induction of transcription at the MMTV promoter (24).…”
Section: Analysis Of Pr Ligand Binding In Cytosolic and Nuclearmentioning
confidence: 99%